Енергія життя після здобуття перемоги & Впровадження синергетичних підходів у процес навчання зростаючого покоління та діяльність дорослих - Салагуб, Людмила Іванівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
I In intelligence, attention is emphasized on synergistic practices, the use of which is currently expedient. After winning the Victory, they will also facilitate a practice-oriented familiarization with the educational material. At the same time, one of the prominent places is focusing attention on the emotional state of each individual. The author analyzed creative methods in the context of the representation of educational cases ("My caricature" / "Emotional caricature" / "Emoji", "Viber task" / "Viber correspondence" / "Educational correspondence"). Of great importance is the production of opinions about project-based learning technologies. The challenge and skill of time is highlighted – the ability to think critically and express one’s own statements (narratives of axiological competence). The study focuses on binary/controversial issues.